A single‐center prospective study on the safety of plasma exchange procedures using a double‐viral‐inactivated and prion‐reduced solvent/detergent fresh‐frozen plasma as the replacement fluid in the treatment of thrombotic microangiopathy. Issue 1 (23rd October 2016) - Vendramin, Chiara; McGuckin, Siobhan; Alwan, Ferras; Westwood, John‐Paul; Thomas, Mari; Scully, Marie
Abstract : BACKGROUND: Patients presenting with acute episodes of thrombotic microangiopathies (TMAs) require urgent access to plasma exchange (PEX). OctaplasLG, a solvent/detergent fresh‐frozen plasma product that has undergone viral inactivation and prion reduction step, has been used in our institution since 2013, replacing Octaplas. STUDY DESIGN AND METHODS: We prospectively reviewed 981 PEX procedures where OctaplasLG was the replacement fluid in 90 patients admitted acutely with a TMA presentation within our institution from January 1, 2013, to December 31, 2015. We recorded citrate toxicities, plasma reactions, viral transfer, complications related to central venous catheter, and venous thrombotic events (VTEs). RESULTS: Citrate toxicities were 5.4%, plasma reactions were 2%, and all were classified as Grade 1 or 2. VTE had an incidence of 12.2%, although 50% of the episodes occurred in early remission when patients were not receiving PEX. No line insertions complications were recorded. Line‐associated infections were 2.2%. Hepatitis B and C serology and human immunodeficiency virus (HIV) were checked on admission. There were four patients who may have had passive transient transfer of hepatitis B antibodies from pooled plasma. No hepatitis C or HIV viral transfer was documented after treatment and no seroconversion was detected after treatment. CONCLUSION: Our data have demonstrated that the incidence of complications during PEX is low and using OctaplasLG is comparable to the low incidence of reactions. No cases of anaphylaxis, transfusion‐related acute lung injury, or fatal plasma reactions were seen. There was no evidence of viral transmission or seroconversion after treatment.